A White Paper on the medical and social needs of people with epilepsy and intellectual disability: The Task Force on Intellectual Disabilities and Epilepsy of the International League Against Epilepsy. Issue 12 (6th November 2014) - Kerr, Mike; Linehan, Christine; Thompson, Rose; Mula, Marco; Gil‐Nagal, Antonio; Zuberi, Sameer M.; Glynn, Mike
Summary This White Paper builds on the publication of the International League Against Epilepsy (ILAE) and International Bureau for Epilepsy (IBE) report "Listening for a change—medical and social needs of people with intellectual disability who have epilepsy" (Listening for a change the medical and social needs of people with epilepsy and intellectual disability, ILAE, 2013). The Paper presents an overview of the recommendations of the report, which aim to improve the health and social care of this important population of people with epilepsy worldwide. Actions in four domains are indicated: (1) the development of standards and initiatives that would enhance diagnosis, pathways to investigation, and treatment; (2) the development of guidelines for treatment, specifically best practice in the management of antiepileptic drugs including rescue medication; (3) the development of standards for primary care, multidisciplinary teamwork, and clinical consultations, with emphasis on the need to enhance communication and improve access to information; and (4) the enhancement of links among different stakeholders including medical services, educational establishments, employment services, organizations providing opportunities for social engagement, and family members. The breadth of needs of this population is a challenge to the epilepsy world, spanning all the professional groupings, care providers, and the research modalities in epilepsy.